Dynamic role engine and formation control for cooperating agents - S. Hamidreza, Kasaei; S. Mohammadreza, Kasaei; S. Alireza, Kasaei; Mohsen, Taheri (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.